Nostalgia y nomadismo en María Teresa León. Figuraciones del yo femenino en tres textos del exilio - Bonatto, Virginia (2018)
Nostalgia is one of the characteristics of Maria Teresa León's literary work written in exile. It appears mostly as the longing of the Republican resistance during the Spanish Civil War, and it is present both in fictive and in autobiographical writings. This nostalgic ethos appears in combination with nomadic condition, which is consubstantial to exiled identity, and that becomes enriched by experience and feelings considered, in the present work, as feminine. León's nomadism is both spatial (related to geographical displacement) and identitary. The Self emerging in these narratives appears as multiple and interconnected: as the product of a construction that depends on a plurality of others and on continuous displacements. The purpose of this work is to analyse the emergence of these characteristics in the novels Contra viento y marea (1941) and Juego limpio (1959), and in the autobiography Memoria de la melancolía (1970).